2016
DOI: 10.1177/2381336916661532
|View full text |Cite
|
Sign up to set email alerts
|

ESL Teachers’ Perceptions About English Learners’ Reading Motivation

Abstract: The role of motivation in engaging students in reading activities and thus improving their reading achievement has been widely reported for the past decades. However, despite the increasing numbers of English learners (ELs) in the United States, little is known about how teachers perceive their motivation to read. Focus group methodology was used in this study to explore English as a second language teachers' perceptions of ELs' reading motivation. Three major themes that emerged from our qualitative analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Graded readers are books specifically written for second language readers to provide them with a reading experience at a level of fluency and comfort at par with first language reading (Nation & Ming-Tzu, 1999). This is essential because readers need to have access to the text they read so that they remain motivated and interested in reading (Protacio & Jang, 2016). In other words, graded readers provide the opportunity for language learners to have contact with easy reading materials containing familiar words with a mix of new vocabulary in the target language.…”
Section: The Role Of Graded Readers In Readingmentioning
confidence: 99%
See 1 more Smart Citation
“…Graded readers are books specifically written for second language readers to provide them with a reading experience at a level of fluency and comfort at par with first language reading (Nation & Ming-Tzu, 1999). This is essential because readers need to have access to the text they read so that they remain motivated and interested in reading (Protacio & Jang, 2016). In other words, graded readers provide the opportunity for language learners to have contact with easy reading materials containing familiar words with a mix of new vocabulary in the target language.…”
Section: The Role Of Graded Readers In Readingmentioning
confidence: 99%
“…With regards to this issue, teachers can allow the struggling readers to select the set of graded readers that they would like to read before starting to engage them in the reading intervention sessions. Protacio and Jang (2016) propound the importance of providing accessible reading texts that are of interest to the pupils so that they would be motivated to continue reading. In this way, the participants would not feel bored rereading the same graded readers or reading a material that is not of interest.…”
Section: Group Interview With the Participantsmentioning
confidence: 99%
“…It has also been found that teachers do not perceive motivated and unmotivated students well (Protacio, 2012(Protacio, , 2013Taboada & Buehl, 2012). Though motivation plays a significant role in reading comprehension, there are other factors which affect learners' involvement in reading classes (Protacio & Jang, 2016). In EFL setting, the learners are exposed to target language in very limited domains of life, which hinders their growth of language skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent researchers have reflected on the many instructional challenges ESOL educators face in the classroom (e.g., Gándara, Maxwell-Jolly & Driscoll, 2005;Protacio & Jang, 2016;Senom, Zakaria & Ahmad Shah, 2013;Toledo-López & Pentón Herrera, 2015). Some of the most common challenges presented in the current literature reference the little control ESOL educators have over these situations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Senom, Zakaria, and Ahmad Shah (2013) explain that one common challenge for ESOL educators is the reality shock of transitioning from their idealistic concept of teaching to the reality inside their classrooms. In addition to the reality shock of today's teaching environment, ESOL educators are faced with educating diverse academic levels of proficiency in their classrooms (Toledo-López & Pentón Herrera, 2015), lack of effective instructional resources (Gándara, Maxwell-Jolly & Driscoll, 2005), and finding a balance between curriculum and student motivation (Protacio & Jang, 2016)-all of which make teaching an even more challenging task for novice K-12 educators. The reality is that ESOL teachers face daily challenges that require flexible and innovative thinking, as every ESOL student is different and their instructional and linguistic needs do not fit in a onesize-fits-all approach (Toledo-López & Pentón Herrera, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%